Juvenile hormone-mediated termination of larval diapause in the bamboo borer, Omphisa fuscidentalis - Singtripop T. (2014)
Larvae of the bamboo borer, Omphisa fuscidentalis are in diapause for more than nine months (Singtripop, T., Wanichaneewa, S., Tsuzuki, S., Sakurai, S. 1999. Larval growth and diapause in a tropical moth, Omphisa fuscidentalis Hampson. Zool. Sci. 16, 725-733). To examine the endocrine mechanisms underlying this larval diapause, we assayed the responsiveness of the diapausing larvae to 20-hydroxyecdysone (20E) and a juvenile hormone analogue (JHA: S-methoprene). 20E injection caused the larvae to halt movement, followed by deposition of a pupal cuticle. Topical application of JHA induced pupation in a dose-dependent manner. JHA also induced pupation of the larvae whose brains were removed before JHA application. In those larvae, the prothoracic glands became active and competent to respond to brain extracts within seven days after JHA treatment, and the hemolymph ecdysteroid concentration began to increase 12 days after JHA application. These results indicate that JHA stimulates the prothoracic glands of diapausing Omphisa larvae, terminating larval diapause, in contrast with previous findings that JH inhibits the brain-prothoracic gland axis and thus maintains the larval diapause. Current results therefore suggest a novel regulatory mechanism for larval diapause in this species.